2017
DOI: 10.1177/0333102417703764
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific disruption of the blood-brain barrier following repeated inflammatory dural stimulation in a rat model of chronic trigeminal allodynia

Abstract: Background The blood-brain barrier (BBB) has been hypothesized to play a role in migraine since the late 1970s. Despite this, limited investigation of the BBB in migraine has been conducted. We used the inflammatory soup rat model of trigeminal allodynia, which closely mimics chronic migraine, to determine the impact of repeated dural inflammatory stimulation on BBB permeability. Methods The sodium fluorescein BBB permeability assay was used in multiple brain regions (trigeminal nucleus caudalis (TNC), peria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 59 publications
(81 reference statements)
2
33
1
Order By: Relevance
“…Therefore, changes in permeability at the brainstem, an important target area for headache therapeutics, may be particularly relevant for drug delivery during headache. Although studies done in an inflammation induced model of headache showed changes in BBB permeability in the brainstem, namely the TNC ( Fried et al, 2017 ), our studies revealed that cortical KCl injection did not increase paracellular permeability in the brainstem as measured by 14 C-sucrose. This suggests the possibility of model-specific alterations in BBB permeability.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Therefore, changes in permeability at the brainstem, an important target area for headache therapeutics, may be particularly relevant for drug delivery during headache. Although studies done in an inflammation induced model of headache showed changes in BBB permeability in the brainstem, namely the TNC ( Fried et al, 2017 ), our studies revealed that cortical KCl injection did not increase paracellular permeability in the brainstem as measured by 14 C-sucrose. This suggests the possibility of model-specific alterations in BBB permeability.…”
Section: Discussioncontrasting
confidence: 69%
“…In conditions such as TBI and ischemic stroke, the integrity of the BBB is altered following injury ( Prakash and Carmichael, 2015 ), although this loss of integrity is most often associated with trauma within the CNS rather than with CSD or headache. Additionally, in studies examining primary headache disorders, where no obvious CNS trauma exists, CSD and increased BBB permeability have been shown to occur in some instances (i.e., migraine with aura; Leira et al, 2007 ; Charles and Baca, 2013 ; Fried et al, 2017 ). The data presented here represent the first study examining, concurrently, the temporal occurrence of CSD, nociceptive behaviors, and BBB leak in a CSD-induced model of episodic headache.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attentionally, we chose peripheral administration intervention to suppress IL-18 bioactivity before each IS dural infusion, by considering the particularity of our animal models. Western blot analysis verified the blockade of IL-18 in the medullary dorsal horn, which could be explained by blood-brain barrier (BBB) breakdown due to repeated IS dural stimulation [27] . Glial activation occupied a key position in the BBB modulation [28,29] .…”
Section: Discussionmentioning
confidence: 76%
“…The IS was formulated with histamine, serotonin, and bradykinin of 2 mM each, and prostaglandin E2 (PGE2) of 0.2 mM in 0.9% sterile saline, with a pH of 7.0 ( Figure 1). [31][32][33] A total of six researchers participated in the experiment procedure and were denoted as follows: 1) person in charge of grouping; animal feeder; animal, saline and IS transmitter; 2) electroacupuncture executor; 3) modelmaker; 4) behavioral text; 5) electrophysiological recorder and experienced histopathologist; and 6) data analyst and statistician. Researchers 3, 4, 5, and 6 were blinded to the grouping situation of the rats.…”
Section: Experimental Designmentioning
confidence: 99%